Morphological Changes under Strain for Different Thermoplastic Polyurethanes Monitored by SAXS Related to Strain at Break. Issue 24 (4th November 2015) - Stribeck, Almut; Li, Xuke; Zeinolebadi, Ahmad; Pöselt, Elmar; Eling, Berend; Funari, Sérgio
Abstract : In tensile tests of six different hand‐cast thermoplastic polyurethanes (TPU) with a hard‐segment content = 0.51, the volume fraction of hard domains ( v h ) has been tracked. The materials exhibit a linear increase up to a strain of ≈0.5 (strain‐induced phase separation). Thereafter a linear decrease of v h is indicated. When stretched by 100% about 25% of the initially present hard domains are destroyed. The extrapolation to v h = 0 is close to the elongation at break. Characteristic materials parameters are suggested by the found relation. The tests (maximum strain: 3) are monitored by small‐angle X‐ray scattering. The morphology is closer to particle scattering than that of machine‐processed material. Therefore the longitudinal scattering appears fittable by a 1D statistical model that separates the weak discrete scattering from the height distribution of hard domains, whose weight returns the variation of v h with the strain. All TPUs are based on 4, 4 ′ ‐methylene diphenyl diisocyanate (MDI). The other raw components are systematically varied. Two MDI units determine the height of the average hard domain. The variation of v h with strain is described by a tensile augmentation (in analogy to the tensile strength) which is realized at an end‐of‐growth strain. The following hard domain destruction is governed by a consumption factor. Deviations between extrapolated and measured strain at break may be related to the TPU composition. Abstract : Thermoplastic polyurethanes with 6 standard compositions are strained. The SAXS tracks the change in the morphology. The same simple empirical relationship between the volume fraction of hard domains, v h, and the strain is found for all materials. Extrapolation to v h = 0 is close to the elongation at break.